2017
DOI: 10.1186/s12888-017-1482-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Bengali perceived stress scale among LGBT population

Abstract: BackgroundLesbian, gay, bisexual and transgender (LGBT) population encounter more stressful life circumstances compared to general population. Perceived Stress Scale (PSS) can be a useful tool for measuring their stress. However, psychometric properties of PSS have never been tested on LGBT population.MethodsThis cross sectional study employed a two-stage sampling strategy to collect data from 296 LGBT participants from six divisional districts of Bangladesh. Exploratory (EFA) and confirmatory factor analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
1
31
0
1
Order By: Relevance
“…The study findings of the Hindi PSS-10 revealed a three-component structure which is in variance with previous studies which had supported a two-component structure comprising of "perceived helplessness" and "perceived self-efficacy for coping." [25,26] The three-component structure in our study additionally indicates the presence of "distress. "…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The study findings of the Hindi PSS-10 revealed a three-component structure which is in variance with previous studies which had supported a two-component structure comprising of "perceived helplessness" and "perceived self-efficacy for coping." [25,26] The three-component structure in our study additionally indicates the presence of "distress. "…”
Section: Discussionmentioning
confidence: 56%
“…The amount of total variance explained by the two-component structure was 51%, which is consistent with previously published studies on PSS-10. [25][26] Furthermore, the three-component structure of our study explained 61% of the total variance. Our study found that mean perceived stress level measured by the PSS-10 was 18.69 in men and 19.75 in women.…”
Section: Discussionmentioning
confidence: 65%
“…Three well-known scales, the Generalized Anxiety Disorder 7-item (GAD-7) scale [18], Patient Health Questionnaire (PHQ-9) [19] and Perceived Stress Scale (PSS), were used to assess the anxiety, depression and stress of the respondents [20]. We used the validated Bengali versions of the questionnaires [21,22,23]. All these scales showed acceptable reliability among our participants (Cronbach's Alpha was 0.858, 0.794 and 0.630 respectively for GAD-7, PHQ-9 and PSS scales, respectively).…”
Section: Measurement Of Anxiety Depression and Stressmentioning
confidence: 99%
“…Other studies have demonstrated the feasibility and promise of real time social media sites to study the patient experiences of LGBTQ communities but only in small-scale content analyses, and they did not consider how geographic variation in political identity may shape these experiences [ 31 , 32 ]. In these ways, online social media information from LGBTQ patients can provide researchers with unfiltered accounts of patient experience and help develop an understanding of the complexities surrounding LGBTQ health disparities [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%